Trigeminal neuralgia associated with dural arteriovenous fistula: a case report and literature reviews - Zhou, Hao; Wei, Xingrong; Zeng, Defeng; Zhang, Shuguang; Hu, Xueqian; Wei, Zhenqin; Li, Yang (Frontiers in Neurology, 2023)
Trigeminal neuralgia is a paroxysmal, intense electric shock-like, or knife-like, recurrent pain that affects one or more sense areas of the unilateral facial trigeminal nerve. It can be classified into two groups from an etiological standpoint: primary and secondary. The pain episodes brought on by such vascular compression are still categorized as primary trigeminal neuralgia, despite the fact that microvascular compression of the trigeminal nerve root has now been demonstrated to be the primary cause. A rare and complicated condition known as a dural arteriovenous fistula (DAVF) can irritate the Gasserian ganglion or compress the trigeminal nerve’s root entry zone (REZ), leading to secondary trigeminal neuralgia (TN). At present, the treatment of DAVF-induced trigeminal neuralgia is not conclusive. This article reports a case of DAVF-induced trigeminal neuralgia cured by MVD and reviews the relevant literature.